AJARAN TRI KAYA PARISUDHA SEBAGAI LANDASAN PENDIDIKAN NILAI MORAL DAN ETIKA DALAM MEMBENTUK KARAKTER ANAK - I PUTU GEDE PARMAJAYA (Sekolah Tinggi Agama Hindu Negeri Mpu Kuturan Singaraja, 2017)
The development of Hindu religious education do to prepare humans Hindu quality, which is reflected through the ability to think, communicate and behave in accordance with the identity of Hindu religion which is based on the concept of tri kaya parisudha teachings. Think, speak, do what is good and true is a reflection of moral behavior is a universal human phenomenon as well as a characteristic that distinguishes man from animals. Animals do not have the awareness of good and bad things, and is not acceptable, appropriate and inappropriate is done primarily a moral imperative that the law must be keewajiban man to do good deeds. In the tri kaya parisudhacontaining education moral and ethical values are very deep, as taught in detail to the Hindus to control dasendria (ten senses) which sometimes can not be controlled by man in this life, as a result of the increasing complexity of temptation objects worldly always stimulating the human senses.